Structural biology of gram-positive bacterial adhesins - Vengadesan, Krishnan (Wiley Subscription Services, Inc., A Wiley Company, 2011)
The structural biology of Gram-positive cell surface adhesins is an emerging field of research, whereas Gram-negative pilus assembly and anchoring have been extensively investigated and are well understood. Gram-positive surface proteins known as MSCRAMMs (microbial surface components recognizing adhesive matrix molecules) and individual proteins that assemble into long, hair-like organelles known as pili have similar features at the primary sequence level as well as at the tertiary structural level. Some of these conserved features are essential for their transportation from the cytoplasm and for cell wall anchoring. More importantly, the MSCRAMMs and the individual pilins are assembled with building blocks that are variants of structural modules used for human immunoglobulins. MSCRAMMs target the host's extracellular matrix proteins, such as collagen, fibrinogen, and fibronectin, and they have received considerable attention from structural biologists in the last decade, who have primarily been interested in understanding their interactions with host tissue. The recent focus is on the newly discovered pili of Gram-positive bacteria, and in this review, we highlight the advances in understanding of the individual pilus constituents and their associations and stress the similarities between the individual pilins and surface proteins.